Exploring the perceptions of rural youth not in education, employment or training (NEET) on factors that influence their employability - Tele, Azinga (Department of Social Development, 2017)
Young people in rural areas bear the brunt of unemployment in South Africa. This is because many of them do not have access to the relevant opportunities and information needed to help them transition into adulthood roles and the labour market. The restricted access to opportunities poses as a threat to the successful transition and employability of these young people. This qualitative study explored perceptions of factors affecting employability among a select sample of youth that were not in education employment or training (NEET) from a rural community of Engcobo in the Eastern Cape Province. In-depth-individual interviews were conducted with 19 black African youth comprising of 8 males and 11 females between the ages 18 and 34 years. The research sought to explore the opinions of the youth to inform us of the factors they think influence their employability by adopting an Integrated Model of employability by McQuaid and Lindsey (2005). The study was important in order to gauge the voices of these youth regarding their employability. The researcher explored factors influencing the respondents' entry into employment, the factors useful to their gaining employment and personal experience of their unemployment status. The findings revealed that circumstances leading to youth's unemployment may differ, but the way in which youth experience unemployment remains the same whether young or old. The fact that young people experience unemployment the same shows that being NEET at one stage raises the likelihood of remaining in the NEET for a longer period. The respondents' unemployment status affected their behaviour and the way in which they saw themselves: as not contributing members to their families or society. The findings also revealed that rural young people are not employed mainly due to the scarcity of jobs in their local town. Their low levels of educational attainment and skills sets also played a role in this regard. Social networks play a major role in helping young people find information about employment; however this was restricted to a certain extent for rural youth as access to formal information systems is non-existent. The lack of formal information systems plays a major role in hindering the mobility of the youth, be it in education or finding employment. The factors identified were mostly as a result of personal circumstances that may have led them to leave school and external factors related to the labour market. The following recommendations were provided. Efforts to provide alternative educational and training opportunities to accommodate the lengthened transitions to adulthood of NEET youth from rural areas must be given priority. Technical Vocational Education and Training (TVET) Colleges can be used as a mechanism to achieve this. TVET Colleges must be responsive and cater for the needs of the communities and be more visible and accessible. Equally important is clarifying what options are available for young people in terms of technical, vocational education and training opportunities. As such TVET colleges have to find effective ways to share information with youth from rural areas about the programmes they offer and how to access these. Furthermore, relevant employment opportunities that are in line with the youth's needs and skills sets have to be considered. For instance the government could make agriculture and farming more popular amongst the youth in rural areas. This could be done by providing youth friendly services and information about the use of land. In addition to the use of social networks, formal information systems have to be introduced to rural areas to help facilitate job search. This could include information centres for young employment seekers and access to the internet to help expand their reach. Unemployment serves as a major form of exclusion for youth in society at large. This paper argues for a holistic approach that considers both structural barriers and young people's deficits to design interventions towards education, employment and training.